The Tense and Aspect in Presiden Joko Widodo’s Utterances in His Inauguration Speech - Dewi Nuryanti (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2023)
The aim of the research was to describe the tense and aspects of the President’s utterances during his speech at the inauguration ceremony. It was a kind of descriptive qualitative research method. It only focused on describing tense and aspects in a spoken context. The theory used was a theory about tense and aspect by Saeed, Kreidler, and Comrie. Data were taken from YouTube’s official website. The result of the analysis found that the utterances uttered by President Joko Widodo consist of the future tense with the perfective aspect that shows a future situation or condition that does not exist yet, past tense action and the actions that have stopped or finished, and also present tense. In addition, the aspects found in President’s utterances consist of a progressive aspect with complete and incomplete action with future action that aims to be reached in the future, a perfect aspect with accomplishment action and with a complete action; and a progressive aspect with progressive incomplete actions.